The practice of motivated reasoning: Observing knowledge use in real-world policy processes - Dorren, Lars and Bohme, Mirijam (International Review of Administrative Sciences)
Motivated reasoning theory is a psychological theory that reads that policymakers interpret evidence in ways that fit their preferences rather than assessing it neutrally. The theory is increasingly used to explain policy processes as part of a behavioural approach to public administration, but it has limitations. As psychological research relies on experiments, the question remains what role motivated reasoning plays in real-world policy processes. Based on ethnographic observations collected during the planning phase of a large infrastructure project, this study confirms that motivated reasoning explains how people interpret information. However, it also shows that peoples$1 (Bcontext has a great impact on their reasoning. Ultimately, we suggest that a focus on time and real-world context is essential in understanding processes of reasoning, for which methodological diversification is needed.- Reproduced s
Keywords: Motivated reasoning, Behavioral public, Administration, Decision-making, Ethnography, Infrastructure policy, Policy making